Analisis Permintaan Tahu Di Kecamatan Tenggarong Kabupaten Kutai Kartanegara - Ovigeria Subroto Sinaga; Muhammad Badaruddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Tofu is one of the most widely consumed foodstuffs in Indonesia, enjoyed by nearly all social groups due to its affordability, nutritional value, and availability. As a processed product derived from soybeans, tofu has been an integral part of Indonesian diets for generations, with its consumption evenly distributed across regions. This study focuses on analyzing tofu consumption patterns in the Tenggarong sub-district, Kutai Kartanegara Regency, while specifically examining the influence of tofu and tempeh prices on tofu demand. Tempeh is included in the analysis as a comparative product due to its similarity in raw materials and market segment. The research employs a quantitative approach using multiple linear regression to determine the effect of the independent variables—price of tofu (X1) and price of tempeh (X2)—on the dependent variable, tofu demand (Y). Data were collected from relevant local sources through market surveys and secondary data records. The results indicate that both X1 and X2 have a measurable influence on Y, as reflected in the regression equation: Y = -50,178.37 + 20.48X1 + 2,488.09X2. The positive coefficient for tofu price suggests that, contrary to typical demand theory, an increase in tofu price in this specific market segment is associated with higher demand, which may indicate the influence of perceived quality or brand loyalty. Similarly, the positive coefficient for tempeh price implies that as tempeh becomes more expensive, consumers may substitute it with tofu, thereby increasing tofu demand. These findings highlight unique consumer behavior patterns in Tenggarong that may be influenced by cultural preferences, income stability, and market conditions. The study concludes that price dynamics between tofu and its substitute product, tempeh, play a significant role in shaping tofu consumption.